The Debris Flow Occurred at Ru Secco Creek, Venetian Dolomites, on 4 August 2015: Analysis of the Phenomenon, Its Characteristics and Reproduction by Models - Gregoretti, Carlo; Degetto, Massimo; Bernard, Martino; Boreggio, Mauro (Frontiers in Earth Science, 2018)
On 4 August 2015, a very high intensity storm, 31.5 mm in 20 minutes (94.5 mm/h), hit the massif of Mount Antelao on the Venetian Dolomites triggering three debris flows characterized by high magnitude. Two of them occurred in the historical sites of Rovina di Cancia and Rudan Creek and were stopped by the retaining works upstream the inhabited areas, while the third routed along the Ru Secco Creek and progressively reached the resort area and the village of San Vito di Cadore, causing fatalities and damages. The main triggering factor of the Ru Secco debris flow was a large rock collapse on the northern cliffs of Mount Antelao occurred the previous autumn. The fallen debris material deposited on the Vallon d’Antrimoia inclined plateau at the base of the collapsed cliffs and part reached the Ru Salvela Creek, covering it from the head to the confluence with the Ru Secco Creek. The abundant runoff, caused by the high intensity rainfall on 4 August 2015, mobilized about 52500 m^3 of the debris material laying on the Vallon d’Antrimoia forming a debris flow surge that hit and eroded the debris deposit covering the downstream Ru Salvela Creek, increasing its volume. This debris flow routed downstream the confluence, flooding the parking of a resort area where three people died, and reached the village downstream damaging some buildings. A geomorphological analysis was initially carried out after surveying the whole basin. All liquid and solid-liquid contributions to the phenomenon were recognized together with the areas subjected to erosion and deposition. The elaboration of pre and post-event topographical surveys, provided the map of deposition-erosion depths. Using the rainfall estimated by weather radar and corrected by the nearest rain gauge, about 0.8 km far, we estimated runoff by using a rainfall-runoff model designed for the headwater rocky basins of Dolomites. A triggering model provided the debris flow hydrographs in the initiation areas, routed downstream by means of a cell model. The comparison between the simulated and estimated deposition-erosion pattern resulted satisfactory. The results of the simulation captured, in fact, the main features of the occurred phenomenon.